MANAJEMEN PENDISTRIBUSIAN ZAKAT DI BADAN AMIL ZAKAT NASIONAL (BAZNAS) PROVINSI KALIMANTAN SELATAN - Siti Rahmah; Jumi Herlita (Alhadharah: Jurnal Ilmu Dakwah, 2019)
The management of zakat distribution is very important to ensure that the zakat funds obtained by amil are channeled to the maximum and on target in accordance with sharia principles. This study attempts to analyze the management of zakat distribution in BAZNAS, South Kalimantan Province, covering activities of planning, organizing, implementing / mobilizing, and monitoring the distribution of zakat. This type of research is field research with a qualitative descriptive approach. The results of the study show that BAZNAS of South Kalimantan Province has carried out the distribution management function in accordance with management theory and there are several supporting factors and constraints on the distribution of zakat.